Particularly of description temporal structure of publicistic texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article analyzes logical and philosophic view of idea «time»; defined extra-linguistic condition, which influence at the organization of temporal structure texts of publicistic style.
Keywords: time; temporal; temporal structure texts; publicistic style